Relationship between job stress, work overload, work environment, and employee’s turnover intention: a case study of Philea Resort & Spa, Ayer Keroh, Melaka / Nurmalinda Hisham and Siti Nur Kadriah Sazali - Hisham, Nurmalinda; Sazali, Siti Nur Kadriah (Faculty of Business and Management, 2016)
This research study has been conducted at Philea Resort & Spa, Ayer Keroh, Melaka. This research is a study on “Relationship Between Job Stress, Work Overload, Work Environment, And Employees Turnover Intention: A Case Study of Philea Resort & Spa, Ayer Keroh, Melaka”. The main objective of this study is to determine the relationship between job stress, work overload and work environment towards employees’ turnover intention at Philea Resort & Spa, Ayer Keroh, Melaka. The researchers has adopted the descriptive research in order to conduct the study on the regarding issue. The researchers sampling design is the probability sampling which is the Simple Random Sampling Technique and 108 questionnaires were distributed to the employees at Philea Resort & Spa, Ayer Keroh, Melaka. These employees are the permanent local staffs at Philea Resort & Spa, Ayer Keroh, Melaka which refer to the target population of this study. The questionnaires were distributed according to the number of staff of respective departments during lunch hours. The researchers also adopt Scientific Program of Social Science (SPSS) application to analyze the data that is gathered throughout the research process in order to obtain accurate answer for the questions. From the finding it can be conclude that there is a relationship of job stress and work overload between employees turnover intention at Philea Resort & Spa, Ayer Keroh, Melaka whereas there is no correlation between working environment and employees turnover intention